(3fcJ Ydi bWQ GdfOis - (3GdCfUGQj GdeUQj, CHh eMeO, GHf gTGe, LeGd GdOjf, YHOGddg Hf jhSa Hf CMeO Hf YHOGddg, J (B761 (3g`s ((3Wg Hf CMeO GdbdYLjs)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdYGde GdYdGeI LeGd GdOjf CHh eMeO YHO Gddg Hf jhSa GHf gTGe GdMeO ddg QGaY GdOQLGJ def GfNaV dLdGdgs
(3BNQgG (B:s
(3hCf jcajfG TQ GdMSGO hCf dG jaVMfG jhe GdJfGO Hefg hcQeg Efg GdLhGO GdcQje GdQDha GdQMje hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjeG cKjQGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B: 4 / 147s
(3eYLe GdeDdajf(B: 2 / 305s
(3cTa GdXfhf(B: 2 / 1352s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs